The Effect of Theoretical University Courses Towards Practical Work Result Based on Learning Motivation - Dwi Anggaini; Titi Ratnasari; Miftahul Fikri (Yayasan Ilomata, 2020)
PLN Tertiary Education of Engineering is one of universities that focused on energy and electricity. The type of courses offered in Electrical Engineering major are theoretical courses and practical courses. One of the courses that consist both theoretical and practical courses is Electrical Measurement (EM). PLN Tertiary Education of Engineering suggested that students should apply for theoretical course before starting any practical course, or to take both courses in the same semester. However, there are still students who applied for practical courses before finishing theoretical course. Is there any correlation between theoretical and practical courses, as well as connection between Learning Motivation and Practical Course?. This research is conducted using Two-Way Analysis of Variance (two-way ANOVA) with factorial design of 2x2, and further testing using Tukey’s Range Test using the data of 2018 students’ results who are applying for practical courses with prior theoretical course participation and those without any prior theoretical course participation. Step 1: Data collection; Step 2: Requirement analysis test (normality and homogeneity); Step 3: Validity and Reliability test using learning motivation questionnaires; Step 4: Two-way ANOVA; Step 5: Tukey’s Range Test. Interaction found between EM course and student’s learning motivation towards the result of their EM practical work. This is evident from Fh = 16,66 and Ft = 4,04 at α = 0,05 with Fh > Ft which means H1 is accepted. Therefore, there is an impact between theoretical courses towards practical courses.